START control in yeast - Wittenberg, Curt (Henry Stewart Talks, 2009)
Control of cell proliferation, The budding yeast: Saccharomyces cerevisiae, Why yeast?, The budding yeast life cycle, Placement of START in the cell cycle, Observing START, The G1 Checkpoint, Genetic characterization of START, Interdependency of Cdk1 with other regulators of START, Cyclin-Dependent Protein Kinase (CDK), The cyclin/CDK cycle, G1 cyclin/CDK is essential for START, The role of CDK in START, Cell cycle dependent expression of Far1 and cyclins, Periodic accumulation of yeast cell cycle regulators, The molecular correlate of START, G1-specific transcription, G1-specific gene expression and human cancer, The molecular determinant of START, Physiological regulators of START, Mating generates diploid cells from two haploid cells, Cells of opposite mating types can conjugate, Stimulation of the mating pheromone cascade elicits three primary responses, Mating pheromone signaling pathway, Mating pheromone promotes G1 phase arrest by activating the Cln/CDK inhibitor, Far1, Regulation of START by other stimuli, Control of START by cell size, The molecular basis for the sizer and timer, What is the signal for achievement of minimum cell size?